Simulation of cold energy storage in a nanomaterial-filled container using the Galerkin method - Nidal H. Abu-Hamdeh; Ali Basem; Hussein A.Z. AL-bonsrulah; Mashhour A. Alazwari; Sherain M.Y. Mohamed; Abdulmalik A. Aljinaidi (Case Studies in Thermal Engineering)
This research examines the transient solidification through a geometrically complex tank containing multiple corners, which hinder uniform cold energy distribution. To improve heat transfer in these regions, tree-shaped fins were integrated into the design. The tank was filled with water (H2O), and thermal conductivity was enhanced by introducing nano-powders. The study primarily focused on two key factors: the shape of the nano-powders and their concentration. Given that conduction dominated the heat transfer process, the governing equations were simplified accordingly. A homogeneous mixture model was applied to estimate the nanomaterial properties, assuming a uniform dispersion of nanoparticles within the fluid. The findings revealed that freezing pure water took approximately 1.36 times longer than water containing nanoparticles, demonstrating the thermal enhancement achieved with nanomaterials. Additionally, the results highlighted the efficacy of additives shape on the freezing rate, with blade-shaped particles accelerating solidification more effectively than cylindrical ones. Specifically, freezing with cylindrical powders required about 1.07 times longer than with blade-shaped powders.